Impact of the human resources management on performance - Santos, David Rodrigues dos (2018)
The purpose of this Work Project is to study the relationship between the Human Resources Management and performance. To find the existence of the previous relationship, a survey was used to test if the HR1 practices would lead to higher levels of job satisfaction and engagement (proximal outcomes) and if the Strength of the HRM system affects these outcomes (job satisfaction and engagement) or moderates the relation between the HR practices and the proximal outcomes. The impact of the HR practices on the organizational performance and the mediation of Strength of the HRM system in this relation was tested. Lastly, the sample was divided in two regional groups, to analyze differences (Western and Developing countries). Results suggest that some HR practices and Strength of the HRM system have impact on the proximal outcomes but Strength of the HRM system does not moderate the relation between HR practices and outcomes. It was also possible to conclude that the Strength of the HRM system mediates the relation between HR practices and organizational performance. With the regional division, it was concluded that the HR practices that previously affected the proximal outcomes changed and Strength of the HRM systems remained significant. In the Western countries, Strength of the HRM system became a moderator between one of the HR practices and Job satisfaction. The regional division didn’t change the relation between the HR practices (independent variable), Strength of the HRM system (mediator) and organizational performance (dependent variable). It was possible to conclude that effectively there is a link between the Human Resources Management (content and process) and performance (proximal and distal).